Analisis Pembelajaran Pada Siswa ABK Dengan Ketunaan ADHD (Attention Deficit Hyperactivity Disorder) Di SDN Batuceper 1 Kota Tangerang - Nurfadhillah, Septy; Hasan, Najib; Ismawanti, Agnes; Akbar, Ahmad Alvinda (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study was to find out how the implementation of inclusion education services, especially ABK with ADHD disabilities held at SDN Batuceper 1 Tangerang City. The method used in this study uses a type of qualitative research with a descriptive method. The subjects of this study were inclusion guidance teachers, homeroom teachers, and grade 1 ADHD students. Data collection techniques include observation, interviews, tests, and documentation. Based on the results of an interview at SDN Batuceper 1.